Secularism, Assimilation and the Crisis of Multiculturalism - Jansen, Yolande (Amsterdam University Press, 2013)
Jansen’s book shows how even the most sophisticated academic views defending secularism and assimilation remain rooted in unexamined ‘modernist dichotomies’ inherited from French (and to some extent, European) modernism.Rainer Bauboeck, European University Institute|"For anyone who seeks to understand the roots of the "deepening crisis of multiculturalism" in Europe, Yolande Jansen's book is required reading. Jansen's brilliant and insightful analysis draws on a variety of fields and lucidly shows how the crisis is a crisis in modernity. Subtly weaving Proust into the argument, she brings a dry subject to life." -- Brian Klug, University of Oxford